Penilaian tingkat kkesuburan tanah kritis di desa kaling, Kabupaten Karanganyar melalui analisis tanah, pertumbuhan dan hasil tanaman - -, Priyono (Exsplorasi, 2008)
The environment damages in In donesia had been known enough including in Central Java that we can recognized and marked by the land-used which is not suits with its ability (without notice the everlasting of environment which supposed to he inherited into the next generation), One of the example of serious land-damage is critical land in Kaling Vulage, Tasikmadu Karanganyar, as the which become location of the research, The purpose of the needs to be held to reach goals such as :1)Evaluate land’s ability and used-dig land fertility level of roof-tile craftsman in Kaling Village; 2) Give the knowledge information to the society of Kaling Village about fertility level decreasing because of carcless land digging. The method of this research is field survey trough experiment of soybean planting (Wilis variety) in the used-dig land of roof-tile craftsman. This research used the design of experiment factorial trough basic program complete random with one treatment factor, that is organic fertilizer’s dose (Blotong), which is consist of 6 degree: 0 ton/ha; 15 ton/ha; 22,5 ton/ha; 37,5 ton/ha, each of the degree repeated 4 time, so we can get the combination behavior of the 24 treatment combinations. Analysis which are done : Land analysis in laboratory especially chemistry such as N total subtance (Kjeldahl); P-vailable (Bray 1 and Bray 2), lans reaction with pH meter, C-organic (burning method); KTK (KTKE method); substance of K, Ca, and Mg (Photometer method). Besides, it is also use analysis of economic suitability (BC ratio), this research was being held since May 1 st 2007 until October 31 st 2007. The result of analysis are: 1) the treatment of organic fertilizer’s dose (blotong) is not give real effect to all of the measured parameter (plant’s high, wet-weight of all plants, the number of empty legumes, dry-weight of seed, the weight of 100 dry-seed, and dry-weight plant); 2) even so, from all of the data we can see that there is tendency increasing of result (plant high, wet-weight of all plants, dry-weight plant, dry-weight of seed, the weight of 100 dry-seed), expect in the number of empty legumes which is decreasing, it means there is increasing og legume’s weight content. With this research result agronomically, we can develop; 3) Land’s research condition before being  planted (without planted) has low nutrtion element, after being planted and being fertilized with blotong and rhizoplus, it increase the nutrition element even still categorized very low (poor/ctitic) of fertility so the maintain for the production plan needs artificial fertilizer, such as TSP, NPK, KCL, ZK, PHONSKA, SP36 and leaf-flower-fruit fertilizer; 4) the highest result of dra seed in Ki teratment (15 ton/ha), that it 6,085 ton/ha and lowest result is Ko () ton/ha), that is 3,743 ton/ha); 5) the organic fertilizer used (one of them is blotong) and soybean plant (nuts which has economic value) and used in plants alternate, strip plant or in critical land such as Kaling Village Tasikmadu Subdistrict, Karanganyar Regency. Keywords : Land damage, critical land, evaluation, land analysis, growth and plant’s